2021
DOI: 10.1111/papr.13046
|View full text |Cite
|
Sign up to set email alerts
|

Chemical neurolysis of the lateral branches of the sacral dorsal rami for the treatment of chronic pain in the sacroiliac joint: Case report and description of the technique

Abstract: RK. Chemical neurolysis of the lateral branches of the sacral dorsal rami for the treatment of chronic pain in the sacroiliac joint: Case report and description of the technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Neurolysis is often employed to alleviate physical compression. It frequently involves procedures such as bone reduction, muscle, and fascia clearance to address the issue 30 . Laparoscopic lumbosacral plexus decompression has gradually received more attention in recent years, which provides a new idea for neurolysis 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Neurolysis is often employed to alleviate physical compression. It frequently involves procedures such as bone reduction, muscle, and fascia clearance to address the issue 30 . Laparoscopic lumbosacral plexus decompression has gradually received more attention in recent years, which provides a new idea for neurolysis 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Risso et al 6 found effective pain control for 6 months in knee osteoarthritis cases using 1.5 cc of 7% glycerinated Phenol in each of the three genicular nerves. Ferraro et al 7 used 0.75 cc of 7% glycerinated phenol for chemical neurolysis of the posterior sacral network in patients with sacro‐iliac joint pain documenting optimal pain relief at 6 months follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…Electrical radiofrequency (RF) ablation removes target nerves and tissues by thermal damage, which is effective in suppressing chronic hip pain, chronic discogenic back pain, chronic thoracic and abdominal pain, and knee osteoarthritis pain ( Davis et al, 2018 ; Kumar et al, 2019 ; Kapural and Deering, 2020 ; Kim et al, 2020 ; Singh et al, 2021 ). Chemical neurolysis uses substances like ethanol or phenol to irreversibly damage peripheral tissues, e.g., celiac plexus for managing chronic upper abdominal pain ( Cornman-Homonoff et al, 2017 ; Sachdev and Gress, 2018 ) and sacral dorsal rami for sacroiliac joint pain ( Nouer Frederico et al, 2021 ). In addition, cryoablation resorts to extreme low temperature (−60 to −100°C) to ablate peripheral tissues for treating pain ( Yasin et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%